Seasonal variation of Pseudomonas aeruginosa in culture positive otitis externa in South East England. Issue 14 (6th July 2018) - Villedieu, A.; Papesh, E.; Weinberg, S. E.; Teare, L.; Radhakrishnan, J.; Elamin, W. F.
Abstract: Otitis externa is the inflammation of the external auditory canal. The disease is common and shows a seasonal variation with a greater incidence in warmer months. Pseudomonas aeruginosa is a common pathogen in otitis externa and in this retrospective study, we show a corresponding seasonal variation in the proportional incidence of P. aeruginosa isolates from otitis externa in South East England. In total 7770 patients were diagnosed with otitis externa over a period of 9 years from January 2008 to December 2016. P. aeruginosa was isolated from 2802 patients (proportional incidence of 36%). Incidence was higher in the months of August, September and October and in patients between 5 and 15 years of age. We postulate a combination of increased contact with water during warm weather in the holiday season and increased rainfall in the preceding season as a putative mechanism for the seasonal trends.